The Role of Salt Production in the Economic Livelihoods of South Sulawesi’s Coastal Farmers - Resmi, Resmi; Yani, Muhammad; Damayanti, Putri; Ali, Siti Arisya Nurfika; Renaldi, Renaldi (Scieclouds Publishing, 2024)
Various methods were used in this qualitative research to understand how salt production affects South Sulawesi coastal farmers' economic sustainability in Indonesia. The paper investigates the socio-economic factors of salt farming as it studies the obstacles and prospects of small-scale salt producers in Takalar district together with Makassar district and Pangkep district. The authors conducted structured interviews with 30 salt farmers along with participant observation and focus groups to identify crucial economic determinants in salt farming such as market availability and natural changes and gender-related elements. The findings show salt farming produces substantial income which faces increasing risks from unsteady weather and insufficient utilization of modern agricultural technology. The research shows women lead a dual role in salt production because they participate in physical labor while also taking leadership positions in running this business sector. The study investigates economic repercussions pertaining to local and regional markets showing salt farming creates strong economic links throughout local social structures together with broader market systems. Research on small-scale salt production remains limited but this investigation adds important knowledge about sector support which could lead to lasting sustainability by studying neglected areas in coastal Indonesian agricultural economy investigation.